2005
DOI: 10.1515/ijamh.2005.17.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Chinese immigrants in Hong Kong: A comparison with locally born students and factors associated with their psychological well-being

Abstract: The present research aims to compare the psychological well-being of young Mainland Chinese immigrants and locally born students in Hong Kong and to identify factors that are associated with the psychological well-being of young immigrants. Participants, aged from 12 to 17 years, included 1,109 youngsters born in Hong Kong and 342 new immigrants from Mainland China. Factors examined in this research included individual demographic and socio-economic factors like age, gender, length of residence in the host soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
9
0
4
Order By: Relevance
“…Two studies from South Africa have also examined discrimination in relation to adolescent risk behaviors (Brook et al 2006b; Kalichman et al 2006). Studies in Norway (Oppedal et al 2005), Denmark (Montgomery and Foldspang 2007), the Netherlands (Veling et al 2007; Stevens et al 2005a), Spain (Pantzer et al 2006), Bosnia, Croatia and Austria (Sujoldzic et al 2006), Hong Kong (Lam et al 2005) and Canada (Beiser and Hou 2006; Noh et al 2007; Etowa et al 2007) have examined the association between perceived discrimination and health for multiple immigrant groups.…”
Section: Trends In the Recent Literaturementioning
confidence: 99%
“…Two studies from South Africa have also examined discrimination in relation to adolescent risk behaviors (Brook et al 2006b; Kalichman et al 2006). Studies in Norway (Oppedal et al 2005), Denmark (Montgomery and Foldspang 2007), the Netherlands (Veling et al 2007; Stevens et al 2005a), Spain (Pantzer et al 2006), Bosnia, Croatia and Austria (Sujoldzic et al 2006), Hong Kong (Lam et al 2005) and Canada (Beiser and Hou 2006; Noh et al 2007; Etowa et al 2007) have examined the association between perceived discrimination and health for multiple immigrant groups.…”
Section: Trends In the Recent Literaturementioning
confidence: 99%
“…However, there have been few empirical studies of the prevalence of perceived discrimination and its potential effects on health in Asian countries, even though these countries have pervasive discrimination based on gender, age, education level, birth region, sexual orientation and race or ethnicity [17][20]. Prior studies in Asian countries have focused on the health effects of discriminatory experiences of specific stigmatized groups such as rural to urban migrants in China [21], Japanese Brazilians in Japan[19], and young Mainland Chinese immigrants in Hong Kong [20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in Asian countries have focused on the health effects of discriminatory experiences of specific stigmatized groups such as rural to urban migrants in China [21], Japanese Brazilians in Japan[19], and young Mainland Chinese immigrants in Hong Kong [20]. However, we are unaware of any research on the health effects of perceived discrimination in a general population of an Asian country.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies about health effect of discriminatory experiences were conducted in US or European countries, a growing number of papers indicated that discriminatory experience is associated with high prevalence of poor health conditions in Asian countries such as Japan, Hong Kong and China [11], [12], [13]. In South Korea which has strong patriarchal tradition and pervasive educational inequality [14], [15], [16], Kim and Williams reported that gender and education level are the most common sources of self-reported discriminatory experiences and there is a dose-response relationship between the number of situation of discriminatory experiences and poor self-rated health [17].…”
Section: Introductionmentioning
confidence: 99%